Crooked house - Christie, Agatha, 1890-1976. (New York : HarperPaperbacks, 1991)
The normally pleasant household of the late Aristide Leonides is filled with a mounting terror as it becomes obvious someone in his family has given him a fatal dose of poison.
Young Adult
Keywords: Family -- Fiction; Murder -- Fiction; Family life -- Fiction; Homicide -- Fiction; Mystery fiction; England -- Fiction; England -- Fiction